2010
DOI: 10.1111/j.1432-2277.2010.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation improves response to antiviral treatment for recurrent hepatitis C

Abstract: Summary In immune‐competent patients, higher vitamin D levels predicted sustained viral response (SVR) following interferon (INF) and ribavirin therapy for chronic hepatitis C. This study aimed to verify the influence of vitamin D serum levels and/or vitamin D supplementation in predicting SVR rates for recurrent hepatitis C (RHC). Forty‐two consecutive patients were treated for RHC with combination therapy with INF‐α and ribavirin for 48 weeks. Vitamin D serum levels were measured in all patients before antiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
136
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 37 publications
9
136
1
3
Order By: Relevance
“…Recent in vitro studies have shown that VD acts as an antiviral agent that inhibits hepatitis C virus (HCV) production in a human hepatoma cell line (DiCarlo et al, 2015). In patients with HCV that underwent OLT with subsequent recurrent HCV, high rates of sustained virologic response (SVR) were noted in patients receiving VDS (Abu-Mouch, Fireman, Jarchovsky, Zeina, & Assy, 2011;Bitetto et al, 2011;Iruzubieta et al, 2014).…”
Section: Sustained Virologic Responsementioning
confidence: 99%
“…Recent in vitro studies have shown that VD acts as an antiviral agent that inhibits hepatitis C virus (HCV) production in a human hepatoma cell line (DiCarlo et al, 2015). In patients with HCV that underwent OLT with subsequent recurrent HCV, high rates of sustained virologic response (SVR) were noted in patients receiving VDS (Abu-Mouch, Fireman, Jarchovsky, Zeina, & Assy, 2011;Bitetto et al, 2011;Iruzubieta et al, 2014).…”
Section: Sustained Virologic Responsementioning
confidence: 99%
“…Thus, vitamin D deficiency could contribute to a (5) . On the other hand, Kitson et al (13) and Bitetto et al (4) did not find association between vitamin D serum levels and the degree of liver fibrosis in their studies, in which the contribuiting factors were not clear, with chances of being racial, genetic or methodological differences used in vitamin D analysis. It should be questioned if vitamin D deficiency increases with age and the patients included in the present study should be quite young to assess this relationship.…”
Section: Discussionmentioning
confidence: 93%
“…An independent association between low vitamin D serum level and higher degree of inflammatory activity has been suggested (4,13) . A probable explanation for the association between lower vitamin D levels and lower inflammatory activity in the liver would be the decrease of 25-hydroxylase activity, promoting decrease in vitamin D hydroxylation activity and, hence, lower serum levels (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Petta et al, [26] demonstrated that low serum 25-OHD levels were associated with risk of severe fibrosis and low sustained viral response to interferon treatment in patients chronically infected with genotype 1 hepatitis C virus. Another study also showed that vitamin D supplementation improves response to antiviral treatment for recurrent hepatitis C [27]. Vitamin D is linked not only to liver fibrosis but also to liver cirrhosis.…”
Section: Discussionmentioning
confidence: 98%